2017
DOI: 10.3233/jad-160847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vascular Risk Factors on the Progression of Mild Alzheimer’s Disease and Lewy Body Dementia

Abstract: With the exception of smoking, VRF at time of dementia diagnosis were not associated with a more rapid cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 48 publications
6
15
0
2
Order By: Relevance
“…Vascular risk factors and diseases were frequent in the study sample and comparable to other studies [ 11 , 13 ]. In comparison with elderly participants in a Norwegian population study [ 42 ], the prevalence of diabetes and hypercholesterolemia was similar, while hypertension, coronary artery disease and strokes were more common among our study patients.…”
Section: Discussionsupporting
confidence: 90%
“…Vascular risk factors and diseases were frequent in the study sample and comparable to other studies [ 11 , 13 ]. In comparison with elderly participants in a Norwegian population study [ 42 ], the prevalence of diabetes and hypercholesterolemia was similar, while hypertension, coronary artery disease and strokes were more common among our study patients.…”
Section: Discussionsupporting
confidence: 90%
“…This is why we performed a specifically targeted umbrella review to identify the 7 risk factors proven to be associated with VaD and used these factors to estimate our PARs. It is highly probable that each type of dementia is associated with a single specific pattern of risk factors [ 25 , 26 , 27 , 28 ]. Diabetes mellitus, educational level, and depression have, in fact, a quite different weight as risk factors for either AD or VaD (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…So, this increase is linked to the LBP itself and not always related to the association with CAA [20]. Some previous studies have not found differences in vascular risk factors between AD and LBD patients [21,22]. However, the incidence of arterial hypertension and older age was found to be statistically more frequent in LBD when compared to non-demented patients [11].…”
Section: Discussionmentioning
confidence: 99%